Evaluasi Manajemen Sumber Daya Teknologi Informasi Pada Dinas Komunikasi Dan Informatika Probolinggo Menggunakan Kerangka Kerja COBIT 5 - Muhammad Oktoda Noorrohman; Suprapto Suprapto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Office of Communication and Informatics Probolinggo is an organization that serves the community function professionally in the field of information and communication that always improve professionalism for vision, mission and goals that have been achieved by the organization. In the performance there are still some obstacles in human resource management and information technology infrastructure such as investment management issued is still not in accordance with the benefits and results in the can, lack of human resources in activities that cause other personnel to work two jobs, master plan still not yet optimal, but the planning office system because of its broad base and no grip, planning in the IT field itself still follow local government plan. It is necessary to evaluate the level of information technology resource capability using the framework COBIT 5. To determine the Capability Level values ​​on the EDM04 subdomains, APO07, BAI09 and DSS01. The results of questionnaire analysis, interviews and observations obtained value of Capability Level on EDM 04 domain Ensure Resource Optimization at level 2, APO 07 Manage Human Resources at level 2, BAI 09 Manage Assets are at level 1 and DSS 01 Manage Operations are at level 1 in each domain has a gap or gap value 1.